Two-rooted maxillary central incisor incidental finding in CBCT - Tehrani, Sanaz Heidarkhan; Siavoshani, Mehdi Amiri; Amirreza Mehdizadeh; Sana Baghizadeh (Universitas Airlangga, 2025)
Background: Understanding the intricacies of the root canal system and its anatomical/morphological diversities is vital for achieving optimal results in root canal treatments. The effectiveness of endodontic therapy is a function of a comprehensive understanding of tooth anatomy and its potential alterations. Purpose: This case presents the importance of 3D radiography for endodontic diagnostic and treatment planning. The availability of 3D radiography has significantly enhanced endodontics’ diagnostic and curing planning aspects. Case: A female patient was referred for radiographic evaluation of her remaining teeth and edentulous area for implant placement. Case Management: Evaluation was conducted by cone-beam computed tomography using Paxi3D with field of view (FOV) 9*12,200 micrometer resolution. A maxillary central incisor with two distinct roots and root canals was identified and discovered by a 3D radiography. Discussion: Given the infrequent occurrence of two-rooted maxillary central incisors, conducting a thorough radiological and clinical inspection before starting endodontic treatment is of great necessity.